2018
DOI: 10.3892/etm.2018.6291
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor‑21 is a potential diagnostic factor for patients with gestational diabetes mellitus

Abstract: Gestational diabetes mellitus (GDM) is a metabolic disease with symptoms of hyperglycemia, insulin resistance and fetal maldevelopment. Evidence has indicated that fibroblast growth factor (FGF)-21 is a multifunctional protein and exhibits potential therapeutic value for metabolic diseases. The present study investigated the diagnostic value of FGF-21 serum levels in patients with GDM (n=50) and age-matched healthy individuals (n=50). It was demonstrated that the gene and protein expression levels of FGF-21 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…FGF21 stimulates glucose uptake and thermogenesis in BAT whilst in WAT it attenuates lipolysis and increases glucose uptake and adiponectin secretion. 55 On the contrary, a recent study by Xu C et al 57 involving 100 subjects reported that serum FGF21 levels were lower in patients with GDM compared to those in healthy individuals. In the pancreas, FGF21 enhances β cell survival and improves glucose-stimulated insulin secretion.…”
Section: Studies With a Significant Difference In Circulating Fgf21mentioning
confidence: 89%
See 1 more Smart Citation
“…FGF21 stimulates glucose uptake and thermogenesis in BAT whilst in WAT it attenuates lipolysis and increases glucose uptake and adiponectin secretion. 55 On the contrary, a recent study by Xu C et al 57 involving 100 subjects reported that serum FGF21 levels were lower in patients with GDM compared to those in healthy individuals. In the pancreas, FGF21 enhances β cell survival and improves glucose-stimulated insulin secretion.…”
Section: Studies With a Significant Difference In Circulating Fgf21mentioning
confidence: 89%
“…However, further studies are needed to elucidate the basis of elevated FGF21 levels in GDM and whether FGF21 resistance exists in GDM. 55 On the contrary, a recent study by Xu C et al 57 involving 100 subjects reported that serum FGF21 levels were lower in patients with GDM compared to those in healthy individuals. However, in that study, the control group was not pregnant, which was a major limitation.…”
Section: Studies With a Significant Difference In Circulating Fgf21mentioning
confidence: 89%
“…However, it may not be a major factor in the pathogenesis of GDM [ 164 ]. In addition, reduced serum FGF21 levels in GDM patients were shown by Xu et al [ 165 ]. However, a major limitation of this study is that the control group was not pregnant, so it cannot be compared to previous studies.…”
Section: Biomoleculesmentioning
confidence: 92%
“…The sensitivity could have been limited by the variability and quality of samples and detection method, and specificity could have decreased since most biomarkers point out common diabesogenic processes (i.e., insulin resistance, inflammation). In this regard, FGF-21 [148, 169], visfatin [127, 170], IL-6 [119, 171] and resistin [128, 129] displayed variable levels depending on pregnancy phase, and afamin, among others, could serve also as a valid biomarker for other complicated pregnancies, like those with preeclampsia [149]. In this line, GDM patients with cardiovascular risk could be classified by testing biomarkers with key roles on cardiovascular pathophysiology.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%